Содержание субпопуляций антигенов СD16+, СD25+, СD95+ лимфоцитов в периферической крови больных злокачественными эпителиальными опухолями век - Сафроненкова, И.А.; Елагина, В.А. (Таврический медико-биологический вестник, 2012)
У 165 хворих на злоякісні епітеліальні пухлини повік (ЗЄП) повік і у 28 умовно здорових осіб
вивчено рівень експресії антигенів субпопуляцій СD16+, СD25+, СD95+ лімфоцитів за допомогою
однойменних моноклональних антитіл. Встановлено достовірне підвищення рівня експресії антигена
СD25+ і СD95+, і зниження експресії антигена СD16+ при рецидивах ЗЄП у порівнянні з нормою та
безрецидивним перебігом пухлинного процесу. Це свідчить про зниження протипухлинного імунітету
та придбанні здатності імунної системи до стимуляції росту пухлинних клітин. There was studied the expressional level of subpopulation of СD16+, СD25+, СD95+ lymphocytes in 165
patients with malignant epithelial tumors (MET) of the eyelids and in 28 conditionally healthy persons using the
same monoclonal antibodies. It has been established the significant increasing of antigens СD25+ and СD95+
expression and decreasing of СD16+ expression at recurrence of MET of eyelid in comparison with normal
and recurrence-free tumor. It testifies to the decreasing of antitumor immunity in patients with MET of the
eyelids and to acquisition of ability of immune system to stimulation of growth of tumoral cells.